New Paradigm of Learning Islamic Religious Education in the 21st Century: a Study of Amin Abdullah's Thought (Program Studi Pendidikan Agama Islam, 2023)
This research aims to explore Amin Abdullah's thoughts regarding the new paradigm of Islamic Religious Education (PAI) in the 21st century. The aim of this research is to contribute to learning for Islamic Religious Education teachers to be more open to knowledge outside their field. As such, in the learning process, they are more creative in applying approaches and methods in learning tools, processes, and evaluation. The method used in this research was a literature study, which analyzed research results from journals, proceedings, and books with the same theme. For its analysis, this research used a relatively new book by Amin Abdullah, i.e.,